Too hot to thrive: a qualitative inquiry of community perspectives on the effect of high ambient temperature on postpartum women and neonates in Kilifi, Kenya - Adelaide Lusambili; Sari Kovats; Britt Nakstad; Veronique Filippi; Peter Khaemba; Nathalie Roos; Cherie Part; Stanley Luchters; Matthew Chersich; Jeremy Hess; Kadidiatou Kadio; Fiona Scorgie (BMC Pediatrics, 2024)
Abstract Objective To understand community perspectives on the effects of high ambient temperature on the health and wellbeing of neonates, and impacts on post-partum women and infant care in Kilifi. Design Qualitative study using key informant interviews, in-depth interviews and focus group discussions with pregnant and postpartum women (n = 22), mothers-in-law (n = 19), male spouses (n = 20), community health volunteers (CHVs) (n = 22) and stakeholders from health and government ministries (n = 16). Settings We conducted our research in Kilifi County in Kenya’s Coast Province. The area is largely rural and during summer, air temperatures can reach 37˚C and rarely go below 23˚C. Data analysis Data were analyzed in NVivo 12, using both inductive and deductive approaches. Results High ambient temperature is perceived by community members to have direct and indirect health pathways in pregnancy and postpartum periods, including on the neonates. The direct impacts include injuries on the neonate’s skin and in the mouth, leading to discomfort and affecting breastfeeding and sleeping. Participants described babies as “having no peace”. Heat effects were perceived to be amplified by indoor air pollution and heat from indoor cooking fires. Community members believed that exclusive breastfeeding was not practical in conditions of extreme heat because it lowered breast milk production, which was, in turn, linked to a low scarcity of food and time spend by mothers away from their neonates performing household chores. Kangaroo Mother Care (KMC) was also negatively affected. Participants reported that postpartum women took longer to heal in the heat, were exhausted most of the time and tended not to attend postnatal care. Conclusions High ambient temperatures affect postpartum women and their neonates through direct and indirect pathways. Discomfort makes it difficult for the mother to care for the baby. Multi-sectoral policies and programs are required to mitigate the negative impacts of high ambient temperatures on maternal and neonatal health in rural Kilifi and similar settings.